Enhancement of Energy Properties of Leucaena Leucocephala Pellets via Torrefaction and its Non-Isothermal Decomposition Kinetics - Matali, S.; A. Rahman, N.; S. Idris, S.; Yaacob, N. (International Journal of Engineering and Technology, 2018)
The quality of raw woody biomass as biofuels can be greatly improved by applying a suitable pre-treatment either by thermochemical or biochemical conversions. The aim of this work is to investigate the impact of torrefaction parameters i.e. torrefaction temperature and holding time, on short-rotation energy crop pellet, Leucaena Leucocephala (LL) under inert atmosphere. Torrefaction temperature range under study was set between 200 to 300oC with holding times of 30 and 60 minutes. Torrefied biomass pellet was compared to its raw pellet form in terms of mass-energy properties, hardness quality, and their respective kinetic parameters via Kissingerâ€™s method. Results of the study revealed that temperature has a more significant impact on mass-energy index with holding times influence becoming more apparent at higher torrefaction temperature above 250oC. Energy properties were improved significantly in terms of calorific value and energy density.Â Increasing the torrefaction parameters also resulted in the decrease of pelletâ€™s hardness due to increase in brittleness. Under pyrolysis conditions, the activation energy of raw LL was lower at 186 kJ/mol than torrefied samples (200- 272 kJ/mol). The understanding of the torrefied biomass properties and its weight loss kinetics will give better prediction of product quality by varying torrefaction conditions.Â Â